Anti-candidal biofilm potential of solvent extracts of Aeollanthus cucullathus (Ryding) and its chemical analysis. (January 2019) - Ngo-Mback, M.N.L.; MubarakAli, D.; Dongmo, P.M. Jazet; Boyom, F. Fekam; Thajuddin, N.
Abstract: The antifungal drugs available and mostly used for the treatment of candidiasis are facing fungal resistance, toxicity phenomena and they highlight limited antifungal cell targets. The aim of this study is to assess the antibiofilm potential and to determine the chemical content of Aeollanthus cucullathus . The chemical composition was determined using gas chromatography coupled with mass spectrometry and the bioguided fractionation was performed through silica gel column chromatography. The inhibition parameters were determined by micro-dilution technique. The antibiofilm activity was evaluated using 24 wells macroplate antibiofilm inhibition assay. The interpretation of the biofilm inhibition was performed using an Ultra Violet-spectrophotometer and a Confocal Laser Scanning Microscopy for quantitative and qualitative biofilm analysis. The extraction of the secondary metabolites produced a yield ranging from 1.52 up to 11% respectively for organic solvent and water solvent extracts. The chemical analysis revealed the presence of four major compounds; tetratetracontane (17.02% and 28.72%), dodecane, 6-phenyl (10.49%) and 1, 2-Benzenedicarboxylic acid, mono (2-ethyl) (7.36%). Tetratetracontane were found in Hexane and Hexane ethyl acetate extracts respectively with an amount of 17.02% and 28.71%. The minimum inhibitory concentrations ranged from 0.625 up to 5 mg/mL both for Candida albicans and Candida glabrata . The extract inhibited the biofilm formation up to 0.0625 mg/mL for C. albicans and up to 0.10 mg/mL against C. glabrata . Ascorbic acid (17%) and its derivatives (50.76%) were identified in Aeollanthus cucullathus fractions. The results obtained highlighted the preventive potential of Aeollanthus cucullathus against biofilm formation and the presence of potent biomolecules.